薄板翻板机的驱动四杆机构优化设计 - 李长春; 朱彬; 张景春 (Jixie chuandong)
The four-rod driving mechanism for thin board reversing machine was analyzed in this paper. According to the restraint conditions, the size of the mechanism was optimized.